The use of set magnetic teaching aids to improve mathematical communication ability - Pujiastuti, Heni; Haryadi, Rudi; Rosyana, Rizki Fitriani (Unnes Journal of Mathematics Education, 2021)
Mathematical teaching aids are a set of concrete objects designed, created, collected, or arranged on purpose that is used to help instill or develop concepts or principles in mathematics—the purpose of this study to improve students' mathematical communication skills by using teaching aids. The method in this research is a quantitative approach. This type of research is experimental research, where the purpose of this study to examine the effect of teaching aids on students' mathematical communication skills. The study was conducted on 26 students randomly. Students are selected based on scores from the highest to the lowest on their mathematical abilities. The instruments used were the pretest and posttest of the set material in the form of students' mathematical communication skills. Based on the analysis results, set magnetic teaching aids in learning selected material shows a good category. This was obtained from the posttest average score of 86.73. From these results, in general, mathematics learning using set magnetic teaching aids received a positive response; this was seen through the posttest results of students' good communication skills with a percentage of 84.62%.